El hidróxido de calcio en la odontología actual - Yepes-D., Fanny Lucia; Velez-R., Francisco Humberto (Revista Facultad de Odontología Universidad de Antioquia, 2016)
This paper reviews the clinical use of calcium hydroxide since its introduction in the early scientific dentistry. The tissue reactions and therapeutic activity of calcium hidroxide are presented, especially the dentine bridge formation after its use in pulpal exposure. Moreover, it is analized its antibacterial activity, its therapeutic action in the cases of intra-alveolar root fractures, root perforations and the management of both external and internal root resorption. The calcium hydroxide has been used widely in apexification, to get induction of root end closure by hard tissue formation. It is presented a discussion and some controversies supported by the reviewed authors about the use of the calcium hydroxide in restorative dentistry. Despite of the good clinical results obtained with calcium hydroxide, it is necessary a more scientific evaluation, especially about the mechanisms of its effects, because they remain unclear, and it may present confusion at the time of results interpretation.